Hsa_circ_0006988 Promotes Sorafenib Resistance of Hepatocellular Carcinoma by Modulating IGF1 Using miR-15a-5p - Rui Qiu; Zhifeng Zeng (Canadian Journal of Gastroenterology and Hepatology)
Background. Hepatocellular carcinoma (HCC) is the most frequently occurring cancer and contributes to the largest number of cancer-associated deaths worldwide. Recent evidence suggests that circular RNAs (circRNAs), which are critical for HCC etiology and metastasis, are distinctly modulated in HCC. Nevertheless, the underlying mechanism of circRNA-mediated sorafenib resistance (SOR) in HCC is yet to be determined. Methods. The hsa_circ_0006988, IGF1, and miR-15a-5p contents were quantified via ELISA and quantitative real-time polymerase chain reaction (qRT-PCR), respectively. Cell Counting Kit-8 (CCK-8) was used for the IC50 evaluation. Lastly, associations among hsa_circ_0006988, IGF1, and miR-15a-5p were validated through dual-luciferase reporter (DLR) and RNA immunoprecipitation (RIP) assays. Results. Herein, a new circRNA, hsa_circ_0006988, was identified, and its levels were markedly enhanced in SOR-resistant (SOR-R) HCC tissues. Functionally, hsa_circ_0006988 strongly suppressed SOR toxicity in vitro. Our examination of the signaling pathway revealed that hsa_circ_0006988 sequestered miR-15a-5p, a negative modulator of IGF1, thus suggesting that hsa_circ_0006988 deficiency diminished SOR resistance of HCC, and this action utilized the release of excess miR-15a-5p, which suppressed IGF1 levels. Moreover, miR-15a-5p overexpression reversed the hsa_circ_0006988-mediated SOR-R and enhanced IGF1 levels in HCC cells. Conclusion. Hsa_circ_0006988 partly promoted the SOR-R of HCC cells through miR-15a-5p sequestering and upregulation of IGF1 levels.